2016
DOI: 10.1002/jbmr.2873
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Site-Specific Normative Data Curves for HR-pQCT

Abstract: The purpose of this study was to develop age-, site-, and sex-specific centile curves for common high-resolution peripheral quantitative computed tomography (HR-pQCT) and finite-element (FE) parameters for males and females older than 16 years. Participants (n = 866) from the Calgary cohort of the Canadian Multicentre Osteoporosis Study (CaMos) between the ages of 16 and 98 years were included in this study. Participants' nondominant radius and left tibia were scanned using HR-pQCT. Standard and automated segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 42 publications
(93 reference statements)
4
121
3
2
Order By: Relevance
“…Predicted change derived from our previously published cross‐sectional data accurately forecasts rate of change for males’ and females’ total density and cortical thickness at the radius and cortical density at the tibia, in the participants older than 50 years. There are some parameters, including cortical porosity and trabecular area that are not consistent with the cross‐sectional predictions.…”
Section: Discussionmentioning
confidence: 82%
“…Predicted change derived from our previously published cross‐sectional data accurately forecasts rate of change for males’ and females’ total density and cortical thickness at the radius and cortical density at the tibia, in the participants older than 50 years. There are some parameters, including cortical porosity and trabecular area that are not consistent with the cross‐sectional predictions.…”
Section: Discussionmentioning
confidence: 82%
“…(F) HR‐pQCT scans of the distal tibia of patient A1. (G) Bone microstructure parameters of the distal tibia of patients A1, B1, and B2 (carrying heterozygous ENPP1 mutations) obtained by HR‐pQCT in comparison to a healthy sex‐ and age‐matched control group …”
Section: Resultsmentioning
confidence: 99%
“…4D and Supplemental Table S7). Biomechanical findings at 23 weeks continued to exhibit reduced bone (35) stiffness and maximum load but also demonstrated increased ductility, suggesting that the accumulation of unmineralized matrix over time has altered the material properties of bone (Fig. 4E).…”
Section: Murine Phenotype Of Enpp1 Deficiencymentioning
confidence: 97%
“…To further emphasize the clinical significance of these findings, we used differences in T-score between fixed and %-of-length measurements to relate the observed measurement bias to biological variability. While it has been suggested that centile curves, rather than T- or Z-scores, are more appropriate for the clinical application of HR-pQCT [7], our observations suggest that meaningful interpretation of an individual HR-pQCT score will require anatomically standardized measurements, regardless of the score formulation applied. For example, on average the fixed offset measurement of Ct.BMD deviated by 1.0 SD from what would be measured at a standard anatomic %-of-length position.…”
Section: Discussionmentioning
confidence: 71%
“…gender and race comparison studies) and potentially diminishes the statistical power in discriminant analyses. Furthermore the dependence on bone length significantly limits the clinical utility of HR-pQCT for individual assessment of bone quality in patients with body sizes that differ from the mean of the reference population [711]. Adapting scan localization protocols to account for subject-specific limb length would therefore remove an important source of measurement variability, thereby improving the power of this technology in musculoskeletal research and relevance for clinical practice.…”
Section: Introductionmentioning
confidence: 99%